Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting

Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Nanoscale particles for polymer degradation and stabilization-trends and future perspectives - Kumar, Annamalai Pratheep; Depan, Dilip; Tomer, Namrata Singh; Singh, Raj Pal (Progress in Polymer Science, 2009)
The field of nanoscience and nanotechnology is extending the applications of physics, chemistry, biology, engineering and technology into previously unapproached infinitesimal length scales. The polymer-nanoparticles/nanocomposites have been the exponentially growing field of research for developing the materials in last few decades and have been mainly focusing on the structure-property relationships and their development. Since the polymer-nanocomposites have been the staple of modern polymer industry, their durability under various environmental conditions and degradability after their service life are also essential fields of research. Thus, this article is intended to review the status of worldwide research in this aspect. Among various nanoparticulates, clay minerals and carbon nanotubes are more often used in enhancing physical, mechanical and thermal properties of polymers. In very few systems, the nano particulates have been incorporated into polymer as `nano-additives' for both purposes: degradation and stabilization of polymers. The degradation and durability of polymers is reviewed in the presence of nanoparticles/nanocomposites under different environmental conditions. Nanoparticle-induced biodegradation of polymers is also discussed. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotubes; clay; Degradation and stabilization; Nanocomposites; Nanoparticles; Polymer

Preparation and characterization of novel hybrid of bio-assisted mineralized Zn-Al layered double hydroxides using chitosan as a template - Depan, Dilip; Singh, Raj Pal (Journal of Applied Polymer Science, 2010)
The purpose of this study was to prepare and characterize a novel nanohybrid prepared from the template-assisted mineralization of Zn-Al Layered Double Hydroxide (LDH) onto the surface of Chitosan (CSI), with an emphasis on morphology, biocompatibitity, and its use as an efficient drug carrier agent. The as prepared LDH is highly crystalline, with platelet-like morphology and curved tactoids when nucleated onto the surface of CSI. Our results indicate that the -OH and -NH functional moieties on CSI can direct an ordered structure of LDH, due to the electrostatic interaction between biopolymer and inorganic lamellae. We have been successful to intercalate an anti-inflammatory drug, Sodium Ibuprofen (Ibu), into LDH, through conventional coprecipitation method. LDHs are endowed with great potential for delivery vector because their stacked layers lead to safe reservation of biofunctional molecules or genes, and their ion exchangeability and solubility in acidic media (pH < 4) give rise to the controlled release of drug molecules. According to the cell-growth studies, LDHs are found as cell viable up to the concentration of 500 mu g/mL. This study reveals that LDH not only plays a role of a biocompatible-delivery matrix but also facilitates a significant increase in the delivery efficiency. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115:3636-3644,2010
Keywords: bio-assisted mineralization; cell-growth studies; Chitosan; drug delivery systems; layered double hydroxides

Ultrasound-triggered release of ibuprofen from a chitosan-mesoporous silica composite - a novel approach for controlled drug release - Depan, Dilip; Saikia, Lakshi; Singh, Raj Pal (Macromolecular Symposia, 2010)
In this work, an attempt was made to synthesize a novel Chitosan-Mesoporous silica (CS-MS) hybrid composite to design a drug delivery system based on ultrasound triggered stimuli-responsive smart release. The in-vitro drug release properties of both the Mesoporous Silica (MS) and Chitosan (CS) hybrids were investigated. Ibuprofen (Ibu) was used as a model drug. The results from powder X-Ray diffraction (XRD) patterns, and BET N(2) adsorption isotherms exhibited that MS can accommodate drug molecules into the lumen of the channels and pores. Drug release, stimulated by temperature and pH of the release media was also investigated. We studied the Ultrasound (US) triggered release of Ibu in a simulated body fluid (pH 7.4). The results exhibited that US can be used as a non-invasive technique for drug release from polymeric materials. The enhancing effect of ultrasound on drug release is due to the Cavitation effect, without causing any significant destruction on the polymer morphology.
Keywords: Chitosan; drug delivery systems; ibuprofen; Mesoporous silica; Ultrasound

Phytase isozymes from aspergillus niger NCIM 563 under solid state fermentation: biochemical characterization and their correlation with submerged phytases - Bhavsar, Kavita P.; Buddhiwant, Priyanka; Soni, Sarvesh K.; Depan, Dilip; Sarkar, Sampa; Khire, Jayant Malhar (Process Biochemistry, 2013)
Aspergillus niger NCIM 563 produces dissimilar phytase isozymes under solid state and submerged fermentation conditions. Biochemical characterization and applications of phytase Phy III and Phy IV in SSF and their comparison with submerged fermentation Phy I and Phy III were studied. SSF phytases have a higher metabolic potential as compared to SmF. Phy I is tetramer and Phy II, III and IV are monomers. Phy I and IV have pH optima of 2.5 and Phy II and III have pH optima of 5.0 and 5.6, respectively. Phy I, III and IV exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. SSF phytase is less thermostable as compared to SmF phytase. Phy land II show homology with other known phytases while Phy III and IV show no homology with SmF phytases and any other known phytases from the literature suggesting their unique nature. This is the first report about differences among phytase produced under SSF and SmF by A. niger and this study provides basis for explanation of the stability and catalytic differences observed for these enzymes. Exclusive biochemical characteristics and multilevel application of SSF native phytases determine their efficacy and is exceptional. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: A. niger; Isozymes; Phytase; Solid state fermentation; Submerged fermentation